Fault tolerant dynamic control for manipulators - Ramos, Manuel C. Jr (Philippine Engineering Journal)
A fault tolerant manipulator can be expected to perform a desired task even if a joint actuator fails. When a manipulator experiences a joint actuator failure, it can be considered as an underactuated mechanical system. An underactuated serial link manipulator can be controlled by using the coupling effects between links. The control goal to be studied in this paper is to move the end effector from a given initial pose to a specified final pose, after a single joint failure has occurred, where the given robot has at least two degrees of redundancy. The proposed controller is designed based on a reduced order model. The control scheme first moves the actuated joints to the desired positions. An iterative control input is then applied to an actuated joint so that the unactuated joint is asymptotically driven to the desired joint position. The control approach is illustrated by simulating a PUMA 600 Arm.